The effect of combined miR‐200c replacement and cisplatin on apoptosis induction and inhibition of gastric cancer cell line migration. Issue 12 (20th May 2019) - Ghasabi, Mehri; Majidi, Jafar; Mansoori, Behzad; Mohammadi, Ali; Shomali, Navid; Shirafkan, Naghmeh; Baghbani, Elham; Kazemi, Tohid; Baradaran, Behzad
Abstract: One of the major obstacles in the treatment of cancer is resistance to standard chemotherapeutic drugs. According to the numerous reports, miR‐200c is involved in many cancers, especially gastric cancer, and also miR‐200c has been known as an effective factor in the elimination of chemotherapy resistance. The purpose of this study was to explore the potential function and mechanism of miR‐200c and cisplatin in the inhibition of migration and induction of apoptosis in gastric cancer cells. In this study, first, miR‐200c mimics and LNA‐anti‐miR‐200c were transfected into KATOIII cells. Moreover, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay results revealed that increased miR‐200c expression and cisplatin can more inhibited the proliferation of KATOIII cells. MiR‐200c overexpression inhibited the movement of KATOIII cells in wound healing assay. Subsequently, miR‐200c/cisplatin could suppress colony formation in KATOIII cells. To identify a potential miR‐200c target, we investigated the effect of miR‐200c modulation on RhoE, PTEN, VEGFR, and MMP9 expression levels. Increased miR‐200c expression caused a reduction in VEGFR and MMP9 mRNA and protein, suggesting that VEGFR and MMP9 are targets of miR‐200c. In addition, reverse‐transcription polymerase chain reaction assays showed that RhoE is target gene of miR‐200c and LNA‐anti‐miR‐200c suppressed the expression of PTEN. Flow cytometry and 4′, 6‐diamidino‐2‐phenylindole staining analysis indicated that miR‐200c increased the cisplatin‐induced apoptosis which may be associated with suppression of RhoE expression in KATOIII cells, also cell‐cycle analysis showed the arrest of cell‐cycle progression at the G2 phase. These data demonstrated that miR‐200c functioned as a suppressor gene in KATOIII cells. Also, miR‐200c can be a potential therapeutic approach to overcome chemoresistance during cisplatin chemotherapy. Abstract : Gastric cancer is one of the most common malignancy of the digestive system. There are, however, different problems in the common treatment methods, such as resistance to drugs, recurrence, and metastasis in cancerous cells. Therefore, investigation to the use of new treatments like microRNA is more exposure to attention and miRNAs are progressively regarded as potential therapeutic targets. microRNAs are a small noncoding RNA molecule (Heydari et al., 2018, Pathol Oncol Res, 24, 145–151; Jiang et al., 2017, Oncol Rep, 38, 151–158; Y. Liu et al., 2017, Sci Rep, 7, 13598). Our study further revealed that miR‐200c could enhance the sensitivity of gastric cancer cells to cisplatin and also, demonstrated miR‐200c involvement in the regulation of cell proliferation, migration, and apoptosis by targeting relative genes such as VEGFR, MMP9, and RhoE.